SISTEM INFORMASI PENGADAAN DAN PENJUALAN AKSESORIS DAN SPAREPART DI TOKO SATRIA MOTOR ACCESSORIES AND SPAREPART SUPPLYING AND SALES INFORMATION SYSTEM IN SATRIA MOTOR STORE WIDYALITA RINDIANI - , WIDYALITA RINDIANI, Nur Rokhman, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Satria Motor store is a micro business which sells accessories and motorcycle spare parts. In running the business, there are data processing activities which contain supplying data, sales data, and stock data. The data processing produces information on supplying report, sales report, and stock report. It is still done in a conventional manner that is on book report. Along with the advancement of information technology, the need of efficient and effective data processing has become very important, so it could produce the information faster and accurately. Based on the problem above, information system has been built which could process supplying data and sales data by using framework CodeIgniter and programming language such as HMTL, PHP, CSS, Javascript, Jquery, and database MySql. The supplying and sales information system could be used for controlling the supplying data, sales data, and stock data in Satria Motor store Klaten. They could also produce the processing report, sales report, and stock report.